Functional Outcomes of Cruciate-Retaining and Posterior-Stabilized Total Knee Arthroplasty: A Randomized Trial Using the Two-Minute Walk and Timed Up and Go Tests - Sirimahachai, Chonlathit; Haruthaiborrorux, Puri; Naratrikun, Kittipon (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: To compare early postoperative functional recovery in patients undergoing total knee arthroplasty (TKA) using cruciate-retaining (CR) and posterior-stabilized (PS) implant designs, as measured by the Two-Minute Walk Test (2MWT) and Timed Up and Go (TUG) test. Methods: This prospective, double-blind, randomized controlled trial included 80 patients with primary knee osteoarthritis (OA) who underwent unilateral TKA. The patients were randomized to receive either a CR or PS implant from the same manufacturer. All surgeries were performed by a single surgeon using a standardized technique. Functional outcomes were assessed preoperatively and at 2, 6, and 12 weeks postoperatively using the 2MWT and TUG tests. Statistical comparisons between the groups were performed using t-tests and repeated-measures ANOVA. Results: Both groups showed progressive improvement over time. At 12 weeks, the mean increase in 2MWT distance was 32.75 ± 24.55 m for PS and 27.91 ± 15.45 m for CR (p = 0.296). TUG test times also improved, with a decrease of −7.53 ± 7.18 s in the PS group and −8.94 ± 8.45 s in the CR group (p = 0.425). No statistically significant differences were observed between groups at any time point. Both groups exceeded the minimal clinically important difference for the 2MWT. Conclusions: Both the CR and PS implant designs demonstrated comparable early postoperative functional outcomes, as assessed by the 2MWT and TUG tests, without statistically significant differences. While the PS group achieved greater improvements in walking distance, the CR group exhibited superior mobility. These findings indicate that implant design does not substantially affect early functional outcomes following TKA.